Effect of initial stress on the dynamic response of a multi-layered plate-strip subjected to an arbitrary inclined time-harmonic force - Daşdemir, Ahmet (Zielona Góra: Uniwersytet Zielonogórski)
The forced vibration of a multi-layered plate-strip with initial stress under the action of an arbitrary inclined time-harmonic force resting on a rigid foundation is considered. Within the framework of the piecewise homogeneous body model with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies (TLTEWISB), a mathematical modelling is presented in plane strain state.
Keywords: multi-layered plate-strip; Finite Element Method (FEM); initial stress; time-harmonic force